An Update on Nitric Oxide Production and Role Under Phosphorus Scarcity in Plants - Galatro, Andrea; Ramos-Artuso, Facundo; Luquet, Melisa; Buet, Agustina; Simontacchi, Marcela (Frontiers in Plant Science, 2020)
Phosphate (P) is characterized by its low availability and mobility in soils, and also by a high redistribution capacity inside plants. In order to maintain P homeostasis, in conditions of nutrient restriction, plants have developed mechanisms which enable P acquisition from the soil solution, and an efficient reutilization of P already present in plant cells. Nitric oxide (NO) is a bioactive molecule with a plethora of functions in plants. Its endogenous synthesis depends on internal and environmental factors, and is closely tied with nitrogen (N) metabolism. Furthermore, there is evidence demonstrating that N supply affects P homeostasis and that P deficiency impacts on N assimilation. This review will provide an overview on how NO levels in planta are affected by P deficiency, the interrelationship with N metabolism, and a summary of the current understanding about the influence of this reactive nitrogen species over the processes triggered by P starvation, which could modify P use efficiency.